Antiphospholipase A2 Receptor Antibody Levels Predict the Risk of Posttransplantation Recurrence of Membranous Nephropathy. Issue 8 (August 2015) - Quintana, Luis F.; Blasco, Miquel; Seras, Miguel; Pérez, Nuria S.; López-Hoyos, Marcos; Villarroel, Patricia; Rodrigo, Emilio; Viñas, Odette; Ercilla, Guadalupe; Diekmann, Fritz; Gómez-Roman, José J.; Fernandez-Fresnedo, Gema; et al.
<x xml:space="preserve">Abstract</x> Background Secretory phospholipase A2 receptor (PLA2R) is the target antigen of the auto-antibodies produced in most (∼70%) patients with primary membranous nephropathy (pMN). The applicability of anti-PLA2R1 antibody monitoring for the prediction of MN recurrence in kidney transplant recipients still is a matter of debate. Methods We sought to characterize the presence and concentration of anti-PLA2R antibodies by enzyme-linked immunosorbent assay (ELISA) in a cohort of 21 patients with pMN before and after transplantation to evaluate whether anti-PLA2R concentrations could predict pMN recurrence. Results The presence of pMN recurrence was significantly correlated with the existence of a positive ELISA assay at graft biopsy or with high level of anti-PLA2R1 activity before transplantation (P = 0.03). In the receiver operating characteristic analysis, anti-PLA2R levels (cut-off of 45 U/mL) during the pretransplantation period accurately predicted pMN recurrence, with a sensitivity of 85.3%, specificity of 85.1%, negative predictive value of 92%, and an area under the curve of 90.8%. This finding supports the hypothesis that anti-PLA2R cause pMN recurrence in humans and indicates the need to prove in an experimental model. Furthermore, 6 of 7 patients with recurrence were carriers of HLA DQA1* 05:01/05 and DQB1* 02:01, confirming these DQ alleles as those associated with higher anti-PLA2R levels. Conclusions This study is the first to demonstrate pretransplantation circulating anti-PLA2R antibodies in a cohort of renal transplant recipients who prospectively developed recurrent disease. Currently, anti-PLA2R levels measured by ELISA may be a rational tool to establish the risk of MN recurrence in renal allograft recipients.